If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4(v-4)=-6v+26
We move all terms to the left:
-4(v-4)-(-6v+26)=0
We multiply parentheses
-4v-(-6v+26)+16=0
We get rid of parentheses
-4v+6v-26+16=0
We add all the numbers together, and all the variables
2v-10=0
We move all terms containing v to the left, all other terms to the right
2v=10
v=10/2
v=5
| -9v+24=-7(v-4) | | (6y-4)+(5y-3)=180 | | 20×(9x+1)=9560 | | 2v^2+17v+8=0 | | 5(-7x+1)=-380 | | 3(19-11y)+5y=1 | | 4=2(x+8)-8x | | 29=7w+2(w-8) | | 24t-3t=0 | | y=-3+20 | | -23=6(y+7)+7y | | (8x+1)+(11x+8)=180 | | (4x+1)=(x+8) | | X-9=26-4x | | x=18=33 | | -13=5(v-8)-2v | | 8x+x=x-4 | | -2+24=x+9 | | 6=0x+1 | | 3x=31/3 | | 4y+10=3(4y+2) | | 2=(2-3x) | | 10x^2+81=0 | | 5x+x^2-16=0 | | 5x+x2-16=0 | | 4/x=3/11 | | 4(3x+7)=-2(5x+8) | | (m-3)X^2=0 | | -73=15=11x | | 11-x=2(x+5) | | 1/2x+6=3/4x-3 | | Y=8x^2-12x |